2019
DOI: 10.1111/jdv.15978
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world comparative effectiveness of adalimumab, etanercept and methotrexate: a Swedish register analysis

Abstract: Background The advent of biosimilars may render etanercept (ETN) and adalimumab (ADA) viable alternatives to methotrexate (MTX) as first‐line systemics in psoriasis. However, real‐world relative effectiveness data comparing ADA and ETN to MTX are limited. Objective To estimate the relative effectiveness of ADA and ETN compared to MTX. Methods We analysed data from DermaReg, a regional register in Stockholm, Sweden, to estimate drug survival and mean Psoriasis Area and Severity Index (PASI) and Dermatology Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Compared with our findings, a recent Swedish registry study observed a similar median drug survival rate for adalimumab but a worse median discontinuation rate for etanercept (17Á5 months vs. 27Á0 months). 37 A recent analysis of a smaller dataset from the Slovenian psoriasis registry (with regard to IL-17 inhibitors) also found a similar drug survival rate for ustekinumab but lower rates for ixekizumab and secukinumab. 38 Likewise, a recent Italian study found a relatively high survival rate of ustekinumab, 39 similar to the rate for secukinumab, but much higher than the rates for adalimumab, infliximab and etanercept (ixekizumab was not included in the study).…”
Section: Discussionmentioning
confidence: 93%
“…Compared with our findings, a recent Swedish registry study observed a similar median drug survival rate for adalimumab but a worse median discontinuation rate for etanercept (17Á5 months vs. 27Á0 months). 37 A recent analysis of a smaller dataset from the Slovenian psoriasis registry (with regard to IL-17 inhibitors) also found a similar drug survival rate for ustekinumab but lower rates for ixekizumab and secukinumab. 38 Likewise, a recent Italian study found a relatively high survival rate of ustekinumab, 39 similar to the rate for secukinumab, but much higher than the rates for adalimumab, infliximab and etanercept (ixekizumab was not included in the study).…”
Section: Discussionmentioning
confidence: 93%
“…For instance, in psoriasis patients some studies reported more adverse events in female patients [80,81] whereas other studies did not find this association [82]. Similarly, the retention rates of biologicals in psoriasis patients were found to be associated with female sex in some studies [83,84] but not in others [85,86]. The same holds true in rheumatology patients treated with biologicals.…”
Section: Discussionmentioning
confidence: 97%
“…Almost the same proportion of patients discontinued treatment in this group, with a similar median methotrexate drug survival of 11.0 months. Other studies that have investigated methotrexate drug survival in adult patients with psoriasis have reported median drug survivals of 9.15 months [26], 12.1 months [11], 15 months [18], 18 months [13], 21.6 months [16], and 29.3 months [15]. Additionally, mean drug survivals have been reported as 7.7 months [14], 17.2 months [27], 18.8 months [17], and 22.3 months [10].…”
Section: Discussionmentioning
confidence: 99%
“…The median methotrexate drug survival in the present study thus lies on the low end of this spectrum, as half of the patients included had discontinued treatment after 11 months. However, differences in the studies performed make comparisons difficult to interpret, such as the inclusion of patients with different psoriasis types [10][11][12]15,26] versus plaque psoriasis only [14,16,18] and uncertainty for the combination therapy or concomitant folic acid [10][11][12][13][14][15][16]26]. For these aspects, the present cohort was similar to that of Otero and colleagues [16], where patients with plaque psoriasis were prescribed methotrexate monotherapy and folic acid supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation